2018
DOI: 10.1038/s41598-018-28366-1
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression analysis identifies a subset of downregulated miRNAs in ALS motor neuron progenitors

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurological disorder that is characterized by a progressive degeneration of motor neurons (MNs). The pathomechanism underlying the disease is largely unknown, even though increasing evidence suggests that RNA metabolism, including microRNAs (miRNAs) may play an important role. In this study, human ALS induced pluripotent stem cells were differentiated into MN progenitors and their miRNA expression profiles were compared to those of healthy control cells. We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 63 publications
(74 reference statements)
2
59
0
Order By: Relevance
“…More recently, a study on muscle tissue from ALS patients showed upregulated levels of miR-132 and miR-125b [80]. Studies showed that TDP-43 and FUS can function miR-132 and NF-kB pathway activation in microglia can modulate miR-125b in ALS [79][80][81]. Thus, miRNAs could be a potential strategy in the early diagnosis and treatment of ALS.…”
Section: Bdnf Associated Micrornas In Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…More recently, a study on muscle tissue from ALS patients showed upregulated levels of miR-132 and miR-125b [80]. Studies showed that TDP-43 and FUS can function miR-132 and NF-kB pathway activation in microglia can modulate miR-125b in ALS [79][80][81]. Thus, miRNAs could be a potential strategy in the early diagnosis and treatment of ALS.…”
Section: Bdnf Associated Micrornas In Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…; Rizzuti et al. ) for example. Future studies will need to tease apart the factors in our collective secretome responsible for rescue, including the factors contained within the exosomes and within the secretome solution, and those factors that may not be involved in rescue (Maguire ,b).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of miRNAs in ALS have been centered in biomarker discovery [232][233][234][235][236][237] and miRNA activity manipulation for therapeutic designs [234,236,238,239]. For example, miR-27a, miR-34a, miR-155, miR-142-5p, and miR-338-3p have been proposed as biomarkers and potential ALS therapeutic targets, directly or indirectly involved in OS [234,236,238,239].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%